Effect of Activity, Liquidity and Amil Fund on Zakat Fund Growth in National Zakat Institution with Disbursement Efficiency as a Mediating Variable - Mohammad Haris Milianto; Iwan Setiadi (ITB AAS INDONESIA Surakarta, 2026)
The growth of zakat funds at the national level has reflected an increasing trend during the 2019–2022 period, despite persistent macroeconomic instability during the pandemic and post-pandemic periods. Most zakat management organizations experienced significant growth, particularly among National Zakat Institutions (LAZNAS) in Indonesia. However, this trend was not consistent across all LAZNAS, some of them showed inconsistent, declining, or fluctuating growth over the years, raising concerns about institutional effectiveness and sustainability. Zakat disbursement efficiency has emerged as a critical strategic issue in recent years, which is believed to play a crucial role in fostering future zakat fund growth. This study examines the effect of activity, liquidity, and amil fund on zakat fund growth, with disbursement efficiency as a mediating variable that are measured by financial ratios. The research employs an explanatory quantitative method using PLS-SEM via SmartPLS 4.1.0.9 and analyzes secondary data from the audited financial reports of 15 LAZNAS from 2019 to 2022. Findings reveal the activity ratio significantly negatively affects disbursement efficiency, while the amil fund ratio has a significant positive effect. The liquidity ratio shows a non-significant negative impact. Additionally, zakat disbursement efficiency has a non-significant negative effect on zakat fund growth and does not mediate the relationship between financial ratios and growth. These results underscore the need for more efficient, adaptive, and accountable zakat governance, leveraging digital technology and transparency to enhance sustainable zakat fund development.